2007
DOI: 10.1007/s00467-007-0471-9
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C is associated with cardiovascular risk factors and metabolic syndrome in Aboriginal youth

Abstract: Serum concentration of cystatin C, a marker of glomerular filtration, has been associated with incident cardiovascular disease (CVD), although the pathophysiology underlying this association remains unclear. As North American Aboriginal populations are experiencing high prevalence rates of CVD in early adulthood, evaluation of cardiovascular (CV) risk factors in Aboriginal children may provide insight into the early pathophysiology of vascular disease. In this context, we sought to determine whether cystatin C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 35 publications
5
25
1
1
Order By: Relevance
“…The inverse relationships of HDL-C and apoA-I with kidney function agree with some reported data obtained in the whole PREVEND cohort ( 24 ). Apparently opposite fi ndings were found when stratifying subjects without renal insuffi ciency according to plasma cystatin-C levels ( 25 ), although in adolescent American Aboriginals ( 40 ), in subjects with essential hypertension ( 41 ), or in type 2 diabetic individuals ( 42 ) no signifi cant associations of HDL-C with cystatin-C levels could be demonstrated. It was long believed that cystatin C concentration is a good marker of kidney function, being independent of demographic variables such as muscle mass, weight, or disease states.…”
Section: Resultssupporting
confidence: 87%
“…The inverse relationships of HDL-C and apoA-I with kidney function agree with some reported data obtained in the whole PREVEND cohort ( 24 ). Apparently opposite fi ndings were found when stratifying subjects without renal insuffi ciency according to plasma cystatin-C levels ( 25 ), although in adolescent American Aboriginals ( 40 ), in subjects with essential hypertension ( 41 ), or in type 2 diabetic individuals ( 42 ) no signifi cant associations of HDL-C with cystatin-C levels could be demonstrated. It was long believed that cystatin C concentration is a good marker of kidney function, being independent of demographic variables such as muscle mass, weight, or disease states.…”
Section: Resultssupporting
confidence: 87%
“…Our findings of cystatin C based equations being influenced by obesity are supported by other studies [28] including Asian and Indigenous populations [29][30][31]. One observational study of immigrant South Asians was also able to demonstrate that the relationship between increasing adiposity and eGFRcysC was largely explained by factors related with chronic inflammation, including c-reactive protein [30].…”
Section: Discussionsupporting
confidence: 87%
“…One observational study of immigrant South Asians was also able to demonstrate that the relationship between increasing adiposity and eGFRcysC was largely explained by factors related with chronic inflammation, including c-reactive protein [30]. In another study of Indigenous youth, cystatin C was strongly associated with the metabolic syndrome [31]. In contrast to our findings, however, other studies of Asian populations have reported that the combined eGFRcysC+cr equation was superior to eGFRcr [11,32,33].…”
Section: Discussioncontrasting
confidence: 78%
“…42 In persons without DM cystatin C, as a marker of early renal dysfunction, could be on the causal pathway between increased BMI and CAD. 43 In T1D persons higher BMI has been associated with CAC, but its relationship with CAC severity was inverse or nonexistent. 44 In T1D patients, the relationship of glycemia to BMI (and other CVD risk factors) may not be as strong as the association of glycemia to CAD.…”
Section: Discussionmentioning
confidence: 99%